(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Abstract: The article describes the morphological and anatomical structure of plant leaves, their forms, ecological types, and functions. It highlights their roles in photosynthesis, transpiration, and gas exchange, as well as their adaptation to environmental conditions. Additionally, it discusses the evolutionary modifications of leaves, their variations, and practical significance. Аннотация: В статье рассматриваются морфологическое и анатомическое строение листьев растений, их формы, экологические типы и функции. Освещается роль листьев в процессе фотосинтеза, транспирации и газообмена, а также их адаптация к условиям среды. Кроме того, обсуждаются эволюционные изменения листьев, их модификации и практическое значение.